1985
DOI: 10.1002/app.1985.070300821
|View full text |Cite
|
Sign up to set email alerts
|

Plasma polymerization of organosilicon compounds

Abstract: SynopsisPlasma polymerizations in five silicon compounds having chemical formula of (CH3),Si-X--Si(CH,),, X = none, CH2, NH, 0, and S atoms, were investigated by elemental analysis, infrared spectroscopy, and ESCA. The chemical composition of polymers plasma-polymerized was influenced by the X groups in (CH,),Si--X--Si(CH,),.Polymers, when X was S atoms, possessed no sulfur; and X was CH2 groups polymers rich in carbon and hydrogen atoms were formed. Details in chemical composition were discussed by IR and ESC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 10 publications
1
40
0
Order By: Relevance
“…For the main part, IR spectroscopy investigations carried out by other authors [63,68,[116][117][118][119][120][121][122] on film plasma polymerized from HMDSO have produced results similar to Fig. 2.2a.…”
Section: Fabrication and Properties Of Thin Plasma Polymer Films As Asupporting
confidence: 53%
See 1 more Smart Citation
“…For the main part, IR spectroscopy investigations carried out by other authors [63,68,[116][117][118][119][120][121][122] on film plasma polymerized from HMDSO have produced results similar to Fig. 2.2a.…”
Section: Fabrication and Properties Of Thin Plasma Polymer Films As Asupporting
confidence: 53%
“…Due to their large variety of chemical and physical properties, these films have been proposed for very different applications. Otherwise, because of the strong dependence on the deposition properties of films made from these and other monomers, it has been reported that they can also be used as gas separation layers or gas permeation layers [43,[62][63][64][65][66][67][68][69][70][71][72]. Organosilicon monomers like hexamethyldisilazane (HMDSN), hexamethyldisiloxane (HMDSO), vinyltrimethylsilane (VTMS), tetramethylsilane (TMS) or various other silanes, but also ethanes and ethenes as well as fluorocarbons like perfluorobenzene were the main components used.…”
Section: Plasma Polymerizationmentioning
confidence: 99%
“…Plasma‐enhanced chemical vapor deposition (PECVD) using organosilanes as starting materials is a promising method for depositing both inorganic SiO 2 ‐like films and polymer‐like SiO x C y H z films, depending on the plasma composition. SiO 2 and related SiO x C y H z films have found many applications in electronics,1 optics,2 barrier films for food packaging,3 and corrosion protection layers 4. The most utilized organosilicon precursors for the deposition of SiO 2 and related SiO x C y H z films are tetraethoxysilane (TEOS) and hexamethyldisiloxane (HMDSO), either 100% precursor or mixed with oxygen or nitrous oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the fabrication of the device. A plasma-polymerized ®lm (12 nm) of hexamethyldisiloxane (b) [19,20] was deposited on a cleaned glass slide (a). This was subsequently treated with ethylenediamine plasma to introduce amino groups onto the surface of the ®lm (c) [10].…”
Section: Plasma-polymerization Processmentioning
confidence: 99%